2021
DOI: 10.1002/pam.22306
|View full text |Cite
|
Sign up to set email alerts
|

Is College Remediation a Barrier or a Boost? Evidence from the Tennessee SAILS Program

Abstract: Many states are redesigning their college remediation policies to increase postsecondary degree completion. In 2012, Tennessee began waiving college math remediation for high school students who completed a computer‐based remedial math course (SAILS) during their senior year. Using a regression discontinuity design, we find that the high school remedial course did not improve students' math achievement any more than the typical senior year math course (although it did allow students to avoid the cost and dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…For example, the Tennessee Seamless Alignment and Integrated Learning Support (SAILS) program moves developmental math courses from college to high school in order to save students time and money in college. There is evidence documenting the positive effects of this program on improving the enrollment rates in college-level math and credit accumulation (Boatman & Bennett, 2021), although a more recent study suggests that co-requisite remediation may be more effective than high school remediation at supporting college math completion (Kane et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Tennessee Seamless Alignment and Integrated Learning Support (SAILS) program moves developmental math courses from college to high school in order to save students time and money in college. There is evidence documenting the positive effects of this program on improving the enrollment rates in college-level math and credit accumulation (Boatman & Bennett, 2021), although a more recent study suggests that co-requisite remediation may be more effective than high school remediation at supporting college math completion (Kane et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In Tennessee, the transition intervention produced an initial effect of a 30% reduction in developmental math enrollment. But the effect was not the result of improved math skills, as Kane et al (2021) demonstrated using a post-intervention assessment, but due to automatic exemption from DE in college upon successful completion of a transition curriculum in high school. 3 In West Virginia and Florida, transition interventions had no detectable impact on DE enrollment.…”
Section: Existing Evidence On the Effectiveness Of Transition Interve...mentioning
confidence: 91%
“…In addition to Kentucky, state-level transition intervention programs have been evaluated in West Virginia (Pheatt et al, 2016), Florida (Mokher et al, 2018), and Tennessee (Kane et al, 2021). Findings in those states, all based on regression discontinuity (RD) designs, are less promising than in Kentucky.…”
Section: Transition Intervention Implementation In Kentucky and Prior...mentioning
confidence: 99%
See 1 more Smart Citation
“…18 See Teixeira et al (2013), Hoxby and Bulman (2015), and Bound, Lovenheim, and Turner (2010). 19 For example, Bahr (2013;2016) and Carrell and Kurlaender (2016) for California; De Vlieger, Jacob, and Stange (2017) for University of Phoenix; Kane et al (2021) and Boatman and Long (2018) for Tennessee; Liu, Belfield, and Trimble (2015) for North Carolina; and Xu & Dadgar (2018) for Virginia. 20 See Cellini and Turner (2019), Stange (2012), andScott-Clayton andRodriguez (2015) for the United States; Melguizo and Wainer (2015) for Brazil; Shavelson et al (2016), , Saavedra (2009), and Barrera-Osorio and Bayona-Rodriguez (2019) for Colombia.…”
Section: Introductionmentioning
confidence: 99%